Loss of Masculinity as a Face of Masculinity Crises Experienced as a Result of Migration - Mehmet Bozok (Journal of Economy Culture and Society)
The debates on migration and gender in social sciences are a growing field. In recent years, the relations between migration and masculinities have come to the fore in these debates when the field of critical studies on men and masculinities had begun to discuss migrant men. Although they are in dominant positions in patriarchal relations, men and masculinities can experience crises that may undermine these positions. The notion of “masculinity crises” is used to point out the intense discontent in the gender identities of men. With the development of critical studies on men and masculinities, masculinity crises have begun to be discussed in this field. The founding researchers of this field emphasized that a general crisis of masculinity could not be mentioned, but rather certain groups of men experiencing certain crises of masculinity. In the following years, masculinity crises began to be investigated by focusing on different contexts that lead to the crisis, and different groups that experience crisis. One of the dynamics that lead to masculinity crises is migration. In various studies on migration and masculinity, the tensions that migrant men experience have begun to be considered in recent years, adopting different approaches such as dislocation, disempowerment and bargaining. Focusing on such researches, this article proposes considering the situations that produce the tensions and anxieties, which patriarchal masculinities experience, such as loss of power, status and social legitimacy as a result of migration, as masculinity crises experienced as a loss of masculinity.